Ferumoxytol: a new, clinically applicable label for stem-cell tracking in arthritic joints with MRI. (December 2013) - Khurana, Aman; Nejadnik, Hossein; Chapelin, Fanny; Lenkov, Olga; Gawande, Rakhee; Lee, Sungmin; Gupta, Sandeep N; Aflakian, Nooshin; Derugin, Nikita; Messing, Solomon; Lin, Guiting; Lue, Tom F; et al.
Aim: To develop a clinically applicable MRI technique for tracking stem cells in matrix-associated stem-cell implants, using the US FDA-approved iron supplement ferumoxytol.Materials & methods: Ferumoxytol-labeling of adipose-derived stem cells (ADSCs) was optimized in vitro . A total of 11 rats with osteochondral defects of both femurs were implanted with ferumoxytol- or ferumoxides-labeled or unlabeled ADSCs, and underwent MRI up to 4 weeks post matrix-associated stem-cell implant. The signal-to-noise ratio of different matrix-associated stem-cell implant was compared with t -tests and correlated with histopathology.Results: An incubation concentration of 500 µg iron/ml ferumoxytol and 10 µg/ml protamine sulfate led to significant cellular iron uptake, T2 signal effects and unimpaired ADSC viability. In vivo, ferumoxytol- and ferumoxides-labeled ADSCs demonstrated significantly lower signal-to-noise ratio values compared with unlabeled controls (p < 0.01). Histopathology confirmed engraftment of labeled ADSCs, with slow dilution of the iron label over time.Conclusion: Ferumoxytol can be used for in vivo tracking of stem cells with MRI. Original submitted 28 February 2012; Revised submitted 8 November 2012